Multibiomarker responses in danio rerio after exposure to sediment spiked with triclosan - Sager, Emanuel Alejandro (2021)
Triclosan (TCS) is an antimicrobial and antimycotic agent widely used in personal care products. In aquatic environments, both TCS and its biomethylated more persistent form, methyl-triclosan (MeTCS), are usually detected in wastewater effluents and rivers, where are commonly adsorbed to suspended solids and sediments. The aim of this study was to evaluate biochemical and physiological effects in Danio rerio after a short term (2 days) and prolonged (21 days) exposures to sediment spiked with TCS acting as the source of the pollutant in the assay. The activities of catalase (CAT), glutathione-s transferase (GST) and superoxide dismutase (SOD), lipid peroxidation levels (LPO), total capacity against peroxyl radicals (ACAP), and acetylcholinesterase enzymatic activity (AChE) were measured in liver, gills, and brain. Most of TCS on the spiked sediment was biotransformed to MeTCS and promoted different adverse effects on D. rerio. Gills were the most sensitive organ after 2 day-exposure, showing lipid damage and increased SOD activity. After 21 days of exposure, liver was the most sensitive organ, showing lower ACAP, increased LPO levels, and SOD and CAT activities. This is the first study reporting the effects on biochemical markers in D. rerio from a MeTCS sink resulting from sediment spiked with TCS.